Pronounced impairment of B cell differentiation during bone regeneration in adult immune experienced mice - Tchouto, Mireille Ngokingha; Bucher, Christian H.; Mess, Ann-Kathrin; Haas, Simon; Schmidt-Bleek, Katharina; Duda, Georg N.; Beule, Dieter; Milek, Miha (Frontiers in Immunology, 2025)
IntroductionAlterations of the adaptive immune system have been shown to impact bone healing and may result in impaired healing in some patients. Apart from T cells, B cells are the key drivers of adaptive immunity. Therefore, their role in age-associated impairments of bone healing might be essential to understand delays during the healing process. B cells are essential for bone formation, and their dysfunction has been associated with aging or autoimmune diseases. But whether age-associated changes in B cell phenotypes are involved in bone regeneration is unknown.MethodsHere, we aimed to characterize the role of immune aging in B cell phenotypes during the early inflammatory phase of bone healing. By comparing non-immune experienced with young and immune experienced mice we aimed to analyze the effect of gained immune experience on B cells. Our single cell proteo-genomics analysis quantified thousands of transcriptomes of cells that were isolated from post osteotomy hematoma and the proximal and distal bone marrow cavities, and enabled us to evaluate cell proportion, differential gene expression and cell trajectories.ResultsWhile the B cell proportion in young and non-immune experienced animals did not significantly change from 2 to 5 days post osteotomy in the hematoma, we found a significant decrease of the B cell proportion in the immune experienced mice, which was accompanied by the decreased expression of B cell specific genes, suggesting a specific response in immune experienced animals. Furthermore, we detected the most extensive B cell differentiation block in immune-experienced mice compared to non-immune experienced and young animals, predominantly in the transition from immature to mature B cells.DiscussionOur results suggest that the pronounced impairment of B cell production found in immune experienced animals plays an important role in the initial phase leading to delayed bone healing. Therefore, novel therapeutic approaches may be able target the B cell differentiation defect to retain B cell functionality even in the immune experienced setting, which is prone to delayed healing.